Caracterização da narrativa oral de história de indivíduos com transtorno do espectro alcoólico fetal - Ganthous, Giulia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Fetal Alcohol Spectrum Disorders – FASD refers to group of manifestations presented by individuals exposed to maternal alcohol consumption during the pregnancy which includes growth deficit, facial dimorphisms, structural and neurodevelopment changes. Among the observed changes, the ability for oral storytelling has been described as an impaired ability in these individuals. Previous studies in this direction focusing mainly the microstructural aspects of the narrative, reported the semantic impairments presented by this population. The goal of this study was to characterize the oral narrative story of individuals diagnosed with FASD from the macrostructural (typical story narrative elements and the overall coherence) and microstructural aspects of the narrative (productivity and linguistic complexity). Thus, three specific goals were proposed: (1) To compare the aspects macro and microstructural of the oral narrative story of individuals with FASD and the typical development of the language, (2) To compare the macro and microstructural aspects of the oral narrative story of clinical subgroups with FASD, established from the “4 Digit Diagnostic Code” and (3) To investigate if there is relationship between the macro and microstructural aspects of the oral narrative story and the level of commitment of the individuals with FASD, from the score of the main clinical features that define the clinical subgroups diagnose of FASD in the “4 Digit Diagnostic Code”. There were in this study 20 individuals with FASD (AG), from both gender, with ages from 6 to 16, they were compared to 20 individuals with typical language development (CG), similar to the FASD individuals, gender, age and socioeconomic level. The oral narrative was elicited by the book “Frog, where are you?”. The results indicated that the individuals with FASD presented statistically significant differences compared to their pairs, in the macrostructural...

O Transtorno do Espectro Alcoólico Fetal – TEAF refere-se ao grupo de manifestações apresentadas pelos indivíduos expostos ao consumo materno de álcool na gestação, que inclui déficit no crescimento, dismorfismos faciais, alterações estruturais no SNC e neurodesenvolvimentais. Dentre as alterações observadas, a habilidade para a narração oral de histórias tem sido descrita como uma habilidade prejudicada nestes indivíduos. Estudos anteriores nesta direção, contemplando, principalmente, os aspectos microestruturais da narrativa, reportaram os prejuízos semânticos apresentados por essa população. O objetivo deste estudo foi caracterizar a narrativa oral de história de indivíduos com diagnóstico de TEAF, a partir de aspectos macroestruturais (elementos típicos da narrativa de história e o nível de coerência global) e microestruturais da narrativa (produtividade e complexidade linguística). Assim, foram propostos três objetivos específicos, a saber: comparar os aspectos macro e microestruturais da narrativa oral de história dos indivíduos com TEAF e desenvolvimento típico de linguagem; comparar os aspectos macro e microestruturais da narrativa oral de história dos subgrupos clínicos com TEAF, estabelecidos a partir do “4 Digit Diagnostic Code” ; e investigar se há relação entre os aspectos macro e microestruturais da narrativa oral de história e o nível de comprometimento dos indivíduos com TEAF, a partir da pontuação das principais características clínicas que definem o diagnóstico dos subgrupos clínicos do TEAF no “4 Digit Diagnostic Code”. Participaram deste estudo 20 indivíduos com diagnóstico de TEAF (GA), de ambos os gêneros,com idade cronológica entre 6 e 16 anos, que foram comparados a 20 indivíduos com desenvolvimento típico de linguagem (GC), semelhantes aos indivíduos com TEAF, segundo o gênero, idade e nível socioeconômico. A narrativa oral foi eliciada por meio do...
Keywords: Fonoaudiologia; Distúrbios da linguagem; Feto - Efeito das drogas; Linguagem; Drugs Physiological effect